A randomized controlled trial to evaluate the efficacy of metacognitive training for people with schizophrenia applied by mental health nurses: Study protocol - Pinho, Lara Guedes de (2019)
Aim: To evaluate the efficacy of the Portuguese version of the metacognitive training (MCT) programme for schizophrenia and its effects on psychotic symptoms, insight into the disorder and functionality. Design: This is a randomized controlled trial that will be undertaken in six psychiatric institutions in Portugal. Methods: This study was approved in March 2019. The sample will consist of people with schizophrenia. The evaluation instruments will include sociodemographic and clinical questionnaires, the Psychotic Symptom Rating Scales, the Beck Cognitive Insight Scale, the World Health Disability Assessment Schedule, and the Personal and Social Performance Scale, applied to both groups at three different times. In the experimental group, the eight MCT modules will be applied over 4 weeks. Discussion: It is expected that at the end of the programme, the experimental group will have reduced severity of psychotic symptoms and improved insight into the disease and functionality. Impact: Schizophrenia is a severe mental disorder that, in most cases, leads to the deterioration of cognitive and social functioning as a result of psychotic symptoms. Metacognitive training for schizophrenia has been used in several countries, but its efficacy remains unclear. It is a type of programme that consists of changing the cognitive infrastructure of delusions.